The Professional Motivation Among Nursing Staff in Hospitals - Mikužienė, Vaida (Slauga. Mokslas ir praktika, 2020)
Nurses‘ professional motivation remains extremely important in Lithuania. Nurses’ professional motivation is one of the main objectives in the organization‘s management, because nurses are the largest health care personnel group. Diverse and active nurse‘s activities could be possible only if to ensure all the needs and expectations. Aim of the research was to investigate the professional motivation among nursing staff in hospital. There were used quantitative study using an anonymous author‘s survey for the nurses. There were the interviewed the nurses (n = 257) which are working in one of the Klaipedas Hospitals. The results showed that, well satisfied nurses are much more motivated and get along better with others. Not all nurses who participated in the questionnaire survey are motivated to work in the hospital. The training and specialization courses are compensated insufficiently. Nurses‘ dissatisfaction with the work in hospital is related to inadequate salary, lack of bonuses and promotion policies, appreciation, education and career opportunity.